China’s Soft Power Diplomacy in Southeast Asia - Johannes Dragsbaek Schmidt (The Copenhagen Journal of Asian Studies, 2008)
The paper analyses the new geo-political and geo-economic strategic relationship between China and Southeast Asia. Is Chinese soft power encroachment into Southeast Asia creating greater stability, does it jeopardize US interests and what is the impact on the regime-types, economic restructuring, and the state-civil society relationship?